Use of the Educational Portal for Distance Learning (Journal of Information Technologies in Education (ITE), 2008)
It has been solved in 2007-2008 years for masters of faculty of physics, mathematics and computer science of Kherson State University within the limits of a subject “the Technique of teaching of computer science in higher educational institutions” to introduce the Distance learning and training with use the Internet-technologies. The purpose of this subject: studying, analysis, research of methodical and practical decisions of questions in subjects of a is natural-mathematical cycle and use of system MOODLE in training.